(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2016)
This paper deals with the subject of alimony lite under the new Brazilian Civil Procedural Code. It analyses the difficulties and uncertainties that might arise from the current broad concepts of family and kinship, which derive from the modern techniques of human assisted reproduction.